Pendampingan BUMDes dalam Analisis Biaya untuk Program Ketahanan Pangan Ayam Petelur di Desa Srowot Kabupaten Banyumas. - Rini Widianingsih; Warsidi Warsidi; Indah Nuraeni (Jurnal Pengabdian Bisnis dan Akuntansi, 2025)
The laying han farming program is one of the Village Fund–supported initiatives aimed at strengthening the food security and economic development sector in Srowot Village, Banyumas Regency. This program is managed by the Village-Owned Enterprise (BUMDes) as a strategic effort to increase village income and create sustainable local businesses. However, the implementation of the program faces challenges related to inadequate cost calculation and the absence of systematic cost accounting practices, which affect the accuracy of production cost determination and financial decision-making. This community service activity aims to provide mentoring assistance to BUMDes managers in calculating production costs for the laying hen program through the application of cost accounting principles. The implementation method includes problem identification, training on basic cost accounting concepts, hands-on assistance in classifying and calculating production costs, and evaluation of the implementation results. Previous studies indicate that the application of cost accounting and financial mentoring in small-scale enterprises and village-owned enterprises can improve cost efficiency, financial transparency, and business sustainability (Hansen et al., 2018; Mulyadi, 2016; Putra et al., 2021). The results of this activity are expected to enhance the managerial capacity of BUMDes in determining accurate production costs, supporting better financial management and strengthening the sustainability of village-based food sector programs.